Challenges Faced by EFL Undergraduate Students in E-portfolio Writing on Google Sites - Febriana, Mita Ekda; Aridah Aridah; Weningtyas Parama Iswari (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
E-portfolios are increasingly utilized in Indonesian higher education, aligning with the "Merdeka Belajar" initiative. However, limited research explores the qualitative experiences of EFL students navigating the challenges of digital writing within this context. This study addresses this gap by investigating the difficulties encountered by undergraduate students at Mulawarman University when writing e-portfolios using Google Sites. The research employed a qualitative narrative inquiry study approach, involving in-depth interviews with three sixth-semester students and analysis of their e-portfolio submissions. Key findings revealed significant challenges related to organizational structure, writing requirements, complex writing tasks (particularly analytical and reflective writing), grammar concerns and vocabulary limitations. Students employed various coping strategies, including AI assistance, online tools, online resources, and peer feedback. The implications of this study highlight the need for educators to provide explicit guidance on e-portfolio design, address specific writing challenges, and support students in effectively utilizing digital tools for academic writing. Further research could expand the sample size for broader generalizability also explore the impact of targeted pedagogical interventions across different platforms and learning contexts.